2003
DOI: 10.1109/tasc.2003.813657
|View full text |Cite
|
Sign up to set email alerts
|

High quality Nb-based tunnel junctions for high frequency and digital applications

Abstract: A number of new fabrication techniques are developed and optimized in order to fit the requirements of contemporary superconducting electronics. To achieve ultimate performance of integrated submm receivers with operational frequency of 1 THz, tunnel junctions with AlN tunnel barrier having a value as low as 1 m 2 have been developed. High quality characteristics of Nb/AlN/Nb tunnel junctions with = 16 and = 10 m 2 have been demonstrated. Electron Beam Lithography (EBL) in combination with Chemical Mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 11 publications
1
43
0
3
Order By: Relevance
“…The quasiparticle branch of the IVC has a very low sub-gap leakage current and the much higher specific resistance of ~ 3.57 kΩµm 2 shows that the tunnel barrier layer is dominated by ALD-grown Al 2 O 3 instead of the thermal oxidation of the Al wetting layer. The sub-gap resistance R sg ~ 4.5 kΩ was measured at V=π∆/2e ~ 1.8 mV, and the sub-gap/normal-state resistance ratio R sg /R N ≈ 20.5 is comparable to previous reports using AlN tunneling barriers [19,20]. However, I c R N product of the junctions made from the reference trilayer and the ALD trilayer are only about 0.3 mV to 0.5 mV which is a factor of three to five less than that expected from the Ambegaokar-Baratoff formula and/or empirical results compiled from junctions made from Nb/AlAlO x /Nb trilayers with controlled thermal oxidation.…”
Section: Resultssupporting
confidence: 85%
“…The quasiparticle branch of the IVC has a very low sub-gap leakage current and the much higher specific resistance of ~ 3.57 kΩµm 2 shows that the tunnel barrier layer is dominated by ALD-grown Al 2 O 3 instead of the thermal oxidation of the Al wetting layer. The sub-gap resistance R sg ~ 4.5 kΩ was measured at V=π∆/2e ~ 1.8 mV, and the sub-gap/normal-state resistance ratio R sg /R N ≈ 20.5 is comparable to previous reports using AlN tunneling barriers [19,20]. However, I c R N product of the junctions made from the reference trilayer and the ALD trilayer are only about 0.3 mV to 0.5 mV which is a factor of three to five less than that expected from the Ambegaokar-Baratoff formula and/or empirical results compiled from junctions made from Nb/AlAlO x /Nb trilayers with controlled thermal oxidation.…”
Section: Resultssupporting
confidence: 85%
“…Using this new pentalevel process, well defined junction diameters as small as 0. 6 can be achieved using optical lithography. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate the limits of this technology, it is necessary to make junctions of sub-micron area. Dmitriev et al have shown good quality junctions with m [19]. …”
Section: Additional Results and Analysismentioning
confidence: 99%